2006
DOI: 10.1007/s10554-005-9046-7
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative imaging of myocardial infarct in rats with high resolution pinhole SPECT

Abstract: Small animal imaging of cardiovascular disease using single photon emission tomography (SPECT) can be used to provide quantitative measurements of myocardial infarct. The purpose of this study was to demonstrate the accuracy of pinhole SPECT imaging with [ 99m Tc]sestamibi for estimation of infarct size in a rat model of coronary artery disease. Nine rats had their left anterior descending artery ligated to induce a region of myocardial infarct. These animals were injected with 37 MBq [ 99m Tc]sestamibi, and, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
25
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 39 publications
(28 citation statements)
references
References 8 publications
3
25
0
Order By: Relevance
“…The optimal intensity threshold for differentiating infarcted and non-infarcted left ventricular myocardium was found by performing linear regression analyses, as described previously [5]. Briefly, linear regression lines plots of calculated infarct size as a function of measured infarct size were calculated for a range of possible threshold values.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The optimal intensity threshold for differentiating infarcted and non-infarcted left ventricular myocardium was found by performing linear regression analyses, as described previously [5]. Briefly, linear regression lines plots of calculated infarct size as a function of measured infarct size were calculated for a range of possible threshold values.…”
Section: Discussionmentioning
confidence: 99%
“…With such a SPECT system, Acton et al recently demonstrated accurate quantification of infarct sizes in rats, as compared to the gold standard histological staining with triphenyltetrazolium chloride [5]. Compared to rat models, murine models present a number of advantages, including low cost, and the availability of an enormous number of knockout models.…”
mentioning
confidence: 99%
“…Normal rats were imaged using dedicated microPET (Inveon following the described method (13). In brief, activated 18 F fluoride was added to 4.0 mg of pentane-1, 5-diyl bis (4-methylbenzenesulfonate) dissolved in acetonitrile. The reaction mixture was heated for 5 minutes at 90°C.…”
Section: Methodsmentioning
confidence: 99%
“…We compared the defect size on small-animal PET images with the gold standard 2,3,5-triphenyltetrazolium chloride (TTC)-stained images (32,33). In the presence of dehydrogenase enzyme that exists in viable myocardium, TTC is reduced and forms a formazan precipitate that makes viable tissue turn brick-red, whereas nonviable infarcted tissue without dehydrogenase activity remains pale.…”
Section: Small-animal Pet and Quantitative Analysismentioning
confidence: 99%